Small Machine Tools for Small Workpieces Final Report of the DFG Priority Program 1476 - Wulfsberg, Jens Peter; Sanders, Adam.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This contributed volume presents the research results of the program "Small machine tools for small work pieces" (SPP 1476), funded by the German Research Society (DFG). The book contains the final report of the priority program, presenting novel approached for size-adapted, reconfigurable micro machine tools. The target audience primarily comprises research experts and practitioners in the field of micro machine tools, but the book may also be beneficial for graduate students.
Tools -- Actuators -- Additional Modules.
Keywords: Manufactures; Security systems; Multibody systems; Vibration; Mechanics, Applied; Machines, Tools, Processes; Security Science and Technology; Multibody Systems and Mechanical Vibrations